Herramientas web 3.0 y su incidencia en los procesos educativos de la carrera de Pedagogía de las Ciencias Experimentales Informática pertenecientes a la Universidad Técnica de Babahoyo, periodo diciembre 2022 – abril 2023 - Cotto Amaiquema, Kevin Andrés (2023)
In recent years, technology has had a great impact on education, allowing teaching and learning processes to be carried out more efficiently and effectively. The aim of this research is to determine how web 3.0 tools intervene in the learning processes of the Pedagogy of Experimental Computer Science program belonging to Babahoyo Technical University, from December 2022 to April 2023. An inductive-deductive method was chosen to reach conclusions that are coherent and original and that allow for an appropriate interpretation of both theoretical and empirical results. The conclusion drawn is that web 3.0 tools have a positive impact on the quality of educational processes in the Pedagogy of Experimental Computer Science program at Babahoyo Technical University. Additionally, it was found that among the most commonly used tools by students in this program, Google Drive is the leader, as cloud-based storage tools are prioritized due to online work or lack of local storage.